The Corellation Between Emotional Intelligence and Academic Achievement: A Meta Analysis Study - Martaputri, Nurul Aulia; Muhtadi, Ali Aulia; Hukom, Julham Aulia; Samal, Diana Aulia (FKIP Universitas Lampung, 2021)
Meta-Analysis : The Correlation between Emotional Intelligence and Academic Achievement. Until now, there have been many studies related to the relationship between emotional intelligence and academic achievement; However, there are different representations or conclusions regarding the research results. Therefore, this study aims to thoroughly determine the effect of emotional intelligence and academic achievement using a meta-analysis approach. This study analyzed 20 Scupus indexed studies with a sample of 5737 people. To support the accuracy of the analysis results, JASP software is used. The results of the study found that the combined effect size values generated using the random-effect model estimation were (M=0.29) with a standard error (SEM=0.08). This effect size belongs to the small effect category. These findings provide a solid theoretical foundation to improve students’ academic achievement in the future.Keywords: Academic Achievement, Emotional Intelligence, Meta-Analisys.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202102